Unintended rapid repeat pregnancy and low education status: Any role for depression and contraceptive use? - Bennett, Ian M. (2006)
OBJECTIVE: The purpose of this study was to assess the contribution of depressive symptoms and poor contraceptive use early in the first postpartum year to the risk of unintended repeat pregnancy at the end of that year among adults with low educational status (< 12th grade or equivalence). STUDY DESIGN: This was a prospective observational cohort study of 643 sexually active, low-income, inner-city adult women (age ≥ 19) who enrolled prenatally (14.7 ± 6.9 weeks gestational age) and were followed twice after delivery (3.3 ± 1.3 months and 11.0 ± 1.3 months). Associations were assessed by multivariate logistic regression. RESULTS: Low educational status (odds ratio, 2.32; 95% CI, 1.25-4.33) and less effective contraceptive use (odds ratio, 2.31; 95% CI, 1.05-4.51) were associated with unintended pregnancy. Neither depressive symptoms nor contraceptive use reduced the risk of pregnancy that was associated with low educational status. CONCLUSION: Low educational status was associated with more than twice the risk of unintended pregnancy 1 year after delivery. We found no evidence that depression or poor contraceptive use mediate this relationship.